Yankees Sealers: Encounters/Disagreement Around The Tierra Del Fuego And Patagonia - Mayorga Zuñiga, Marcelo Paolo (My University, 2018)
The article discloses and analyzes the interethnic relations that took place between the aborigines of the southernmost part of America and the hunters of marine mammals of the United States that since the end of the 18th century were dedicated to the exploitation of skins of fur seals. Specifically a serie of unpublished contacts between sealers and aborigines yamana, kawesqar and selknam, inhabitants of Patagonia and Tierra del Fuego are recorded. The sources consulted correspond mainly to logbooks of sealing voyages, whose examination has allowed to configure the dynamics of sustained contacts and collecting information referring to the details of the hunting activity.
LOBEROS YANKEES: ENCUENTROS/DESENCUENTROS EN TORNO A LA TIERRA DEL FUEGO Y PATAGONIA
Keywords: Sealers; Kawesqar; Yamana; Selknam